THE QUALITY OF ASSESSMENT INSTRUMENT ON THE IMPLEMENTATION OF INTEGRATED CURRICULUM AT UIN SUSKA RIAU (Program Studi Pendidikan Agama Islam, 2019)
This study aims to determine the quality of assessment in the implementation of UIN Suska Riau curriculum integration and the difference in assessment quality in the implementation of curriculum integration in terms of lecturers’ educational background. This was descriptive quantitative research to explore the data from various informants and resources in accordance with the issues reviewed. Furthermore, the informants in this study were lecturers of UIN Suska Riau. The data were collected using interviews and documentation to find out the results of the study using a test description and to determine the differences of assessment quality in the curriculum integration implementation in terms of lecturers’ educational background seen from the mean (average) of each group. Based on the results of research and analysis, the assessment instrument quality classified as